Two Sprinkler Models in Performance, Quality and Ef ficiency of Water Use in Potato Crops (Solanum tuberosum L.) - Beltrán-Félix, Jesús Alejandro; Sifuentes-Ibarra, Ernesto; Lopez-Valenzuela, Blanca Elvira; Ruiz-Perez, Vladimir; Ruelas Islas, Jesús del Rosario; Ayala-Armenta, Quintín Armando (REVISTA TERRA LATINOAMERICANA, 2025)
The surface area of irrigated potatoes harvested in Mexico is 68 000 ha, of which 64% are irrigated and 36% rainfed with an average yield of 27.4 Mg ha-1 and an economic impact of 11 000 million pesos per year, placing this crop among the five main ones in the country. In the last 10 years, the use of fixed sprinkler systems has increased exponentially, mainly in northwestern irrigation districts. Nonetheless, a lack of scientific information exists on their ef fect on yield, quality, and irrigation water use. Therefore, the objective of the present research is to determine the ef fect of Naan Dan 5022 (A1) and Xcell Wobbler Senninger (A2) sprinklers on water yield, quality and use in Fiana variety of potato crop. The study was performed in Sinaloa, Mexico, on a representative soil of the area, establishing three treatments (T) in a strip of land of 0.12 ha: T1 (A1) sprinkler and T2 (A2) sprinkler. The variables measured were operating pressure, irrigation depth, irrigation uniformity, application ef ficiency, biomass, Normalized Dif ference Vegetation Index (NDVI), yield and tuber quality; the last three variables were subjected to an analysis of variance and a mean test. The estimated yield for the best treatment was 42 Mg ha-1 using Xcell Wobbler sprinkler. At the end of this project, the use of Xcell Wobbler sprinkler is recommended due to its operation reliability at lower pressures and, in general, adapting to specific operating demands of the study area and improving potato crop production in the northern state of Sinaloa.